Linguistic Error Analysis in Students’ Course Assignments: Patterns and Pedagogical Implications - Raed Awadh Saeed Alghatnaini; Bakri Mohammed Bkheit Ahmed; Dewi Chamidah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze linguistic errors occurring in final project presentations by master's students in Arabic Language Education, semester 4, at Maulana Malik Ibrahim State University, Malang. Employing a qualitative approach with a case study design, the research focuses on gaining an in-depth understanding of the complexities of linguistic errors within their natural context. Data sources include both primary data—direct observations during presentation sessions and in-depth interviews with students and their academic supervisors—and secondary data derived from academic documents such as thesis guidelines, teaching materials, and theoretical literature on linguistic errors, including works by Al-Bayyinah (2019), Al-Masri (2020), and Al-Turk (2017) on scientific presentation structures. Data were collected without audio or video recordings to ensure participant privacy and ethical integrity. Data analysis followed the framework of Miles, Huberman, and Saldaña, encompassing data reduction, data display, and conclusion drawing, complemented by Saldaña’s coding cycles involving descriptive, pattern, and thematic coding. Findings revealed various types of linguistic errors, including phonological, morphological, syntactic, semantic, and discourse errors, with major contributing factors being the influence of native language, speaking anxiety, and limited speaking practice in Arabic. The results offer strategic recommendations for curriculum development and pedagogical improvement in graduate-level Arabic language instruction, particularly in strengthening spoken communication skills.